Alignment of Instructional Objectives and Learning Material Organization in Maharah al-Kalam Courses with the Development of Students’ Communicative Competence - Rita Febrianta; Indra Saputra; Nurhasnah; Muslim Jafar; Eka Rizal; Yelfi Dewi S (Al-Muyassar: Journal of Arabic Education, 2026)
This study aims to analyze the alignment between instructional objectives and learning material organization in a Maharah al-Kalam course based on Al-Arabiyyah Bayna Yadayk and the development of students’ communicative competence. A qualitative descriptive approach was employed. Data were collected through document analysis, semi-structured interviews, questionnaires, and documentation involving one Maharah al-Kalam lecturer and twenty-two students of the Arabic Language Education Department. The analyzed documents included the Semester Learning Plan (RPS) and instructional materials used in the course. Data were analyzed using the interactive model of Miles and Huberman and validated through triangulation. The findings indicate that the instructional objectives were aligned with the principles of communicative competence by emphasizing students’ ability to use Arabic in meaningful communicative situations. The learning materials, organized based on Al-Arabiyyah Bayna Yadayk, were structured progressively and contextually, supporting the development of speaking skills through authentic language use. Learning activities such as dialogues, role-plays, discussions, and presentations provided students with opportunities to communicate actively in Arabic. However, several challenges were identified, including differences in prior language proficiency, limited vocabulary mastery, lack of self-confidence, restricted classroom interaction time, and the absence of a supportive Arabic-speaking environment outside the classroom.The novelty of this study lies in its integrated analysis of instructional objectives, learning material organization, and learning implementation in fostering communicative competence in higher education Arabic language learning. The findings contribute to the development of communicative-oriented Maharah al-Kalam instruction.